Catalyzing Investment for Green Growth : The Role of Business Environment and Investment Climate Policy in Environmentally Sustainable Private Sector Development - Saurav, Abhishek (World Bank, Washington, DC, 2021)
Developing countries today confront an unprecedented combination of challenges of the need for inclusive growth, worsening environmental degradation, and the impacts of the Coronavirus (COVID-19) pandemic. A successful response must be founded on the principles of sustainable development, circular economic systems, and green growth. By transforming private sector activity through sustainable investment, countries can accelerate recovery and stimulate growth. Achieving this transformation will require robust environmental policies to address externalities and to drive sustainable investment. This paper considers the unique role that business environment and investment climate policy can play in meeting these goals and transitioning to green private sector growth in developing countries. The paper is organized around three key questions. First, how does a country’s investment climate help enable green economic growth? Second, how can efforts to improve the domestic business environment through business regulation reform take account of the need for environmental protection and sustainability? Third, how can policies related to foreign direct investment (FDI) be adjusted to play a stronger role in promoting sustainable sectors and business practices? Together, the answers to these questions establish key concepts and principles that can make investment climate reform an effective and integral component of a green growth strategy.